Calcium oscillations in HEK293 cells lacking SOCE suggest the existence of a balanced regulation of IP3 production and degradation - Octors, Clara; Yoast, Ryan E.; Emrich, Scott M.; Trebak, Mohamed; Sneyd, James (Frontiers in Systems Biology, 2024)
The concentration of free cytosolic $\ca$ is a critical second messenger in almost every cell type, with the signal often being carried by the period of oscillations, or spikes, in the cytosolic $\ca$ concentration. We have previously studied how $\ca$ influx across the plasma membrane affects the period and shape of $\ca$ oscillations in HEK293 cells (Emrich et al, 2021, Cell Rep., 43, 9, 108760: doi 10.1016/j.celrep.2021.108760). However, our theoretical work was unable to explain how the shape of $\ca$ oscillations could change qualitatively, from thin spikes to broad oscillations, during the course of a single time series. Such qualitative changes in oscillation shape are a common feature of HEK293 cells in which STIM1 and 2 have been knocked out. Here, we present an extended version of our earlier model that suggests that such time-dependent qualitative changes in oscillation shape might be the result of balanced positive and negative feedback from $\ca$ to the production and degradation of inositol trisphosphate.